The Determinant of Audit Delay - Fauziah, Fitri Ella; Murharsito, Murharsito (Eksos, 2023)
This study sought to ascertain and evaluate the impact of proximity to one another, audit committee financial expertise, CEO duality, and the nature of firm activities on the audit delay of state-owned corporations listed on the Indonesia Stock Exchange. In this study, a sample of state-owned businesses was chosen through the use of multiple regression as an analytical technique in conjunction with purposive sampling. The findings revealed that while audit committee expertise had no significant impact on audit delay and that CEO duality had a substantial positive impact, geographic proximity and the nature of the company's activity variables had a significant negative impact on audit time.